Effects of a high‐fat diet on the brain in FRGN mice with humanized livers: Molecular and cell biology/signal transduction. (7th December 2020) - Edlund, Anna K.; Giannisis, Andreas; Patra, Kalicharan; Morrema, Tjado H.J.; Hoozemans, Jeroen J.M.; Bial, Greg; Foquet, Lander; Nielsen, Henrietta M.
Abstract: Background: Diets rich in fat lead to high levels of circulating free fatty acids that induce systemic inflammation, which contribute to systemic insulin resistance and consequently impaired glycemic control. Both of these conditions are associated with brain glucose hypometabolism [1, 2] and an increased risk of neurodegenerative dementias such as Alzheimer's disease. Mice on a high‐fat diet (HFD) were reported to show signs of brain insulin resistance with coinciding cognitive impairment [3]. Due to the significant difference in lipid metabolism between mouse and man, its poorly understood how the effects of a HFD on mice brains translate to human brain. We therefore employ a mouse model with humanized livers resulting in a more human‐like peripheral lipid profile [4] to study the effects of a HFD on the mice brain. Method: FRGN mice with humanized livers were fed either normal chow or a 12‐week HFD. Brains were harvested and divided with a sagittal cut. The right hemispheres were used for immunohistochemical analysis and the left hemisphere was macro‐dissected to retrieve the hippocampus and the cortex which were fractionated into nuclei‐ and synaptosome enriched as well as synaptosome‐depleted tissue fractions using an established differential centrifugation protocol. Tissue fractions were used for western blotting assessment of various markers relevant to insulin signalling, glucose uptake, synaptic integrity and neuroinflammation. Result: Initial results from the immunohistochemical analysis of the cortex reveal near‐abolished levels of the microglial marker IBA1 (model effect) and increased accumulation of reactive astrocytes around blood vessels in FRGN mice compared to WT mice. The GFAP signals were slightly reduced in FRGN mice with humanized livers. Both observations were unrelated to the HFD. Conclusion: Initial results from our immunohistochemical evaluation of the cortex suggest a model‐specific decrease in microglial cells in the FRGN mice, and modest changes in the presence of astrocytes in FRGN mice with humanized livers that appeared unaffected by a HFD. References: (1) Burns, C.M., et al., Neurology, 2013. 80(17): p. 1557‐64. (2) Baker, L.D., et al., Arch Neurol, 2011. 68(1): p. 51‐7. (3) Kothari, V., et al., Biochim Biophys Acta Mol Basis Dis, 2017. 1863(2): p. 499‐508. (4) Ellis, E.C., et al., PLoS One, 2013. 8(11): p. e78550.